Recovery of High Interference Memory in Spite of Lingering Cognitive Deficits in a Longitudinal Pilot Study of Hospitalized Depressed Patients - Han, Xue; Wu, Yingga; Zhong, Yanfeng; Becker, Suzanna (Frontiers in Psychiatry, 2020)
Background: Major depressive disorder has deleterious impacts on mood, cognition, and many functions of daily life. Even after remission of mood symptoms, patients frequently report persistent cognitive deficits. By contrast, the neurogenic theory of depression posits that recovery from depression is dependent upon a restoration of neurogenesis. The present study was designed to test this prediction by assessing performance in MDD in-patients on a broad battery of cognitive tasks including the Mnemonic Similarity Task, a high interference memory test that is a putative correlate of neurogenesis. We predicted that remitted patients should exhibit recovery of function on this task, even though they may show residual deficits on other cognitive tasks. Methods: 18 hospitalized patients diagnosed with MDD and 22 healthy control participants matched for age, sex and education completed a battery of mood and cognitive tests at two time points. Patients completed their baseline assessments when first admitted to hospital, and repeated the same assessments upon remission, typically 4-5 weeks later and just prior to their release from hospital. Control participants were tested at baseline and 4-5 weeks later on the same assessment battery, which included the BDI-II, BAI, Cohen’s PSS, Mnemonic Similarity Task and several sub-tests adapted from the CANTAB. Results: At baseline, MDD patients were impaired relative to controls on the MST and many other cognitive tasks. Upon remission, patients’ MST scores did not differ from those of healthy controls, although patients were still impaired on Pattern Recognition Memory, Spatial Recognition Memory, Delayed Matching to Sample and Paired Associates Learning relative to healthy control participants. Conclusion: The lingering memory deficits observed in remitted patients with MDD observed here are broadly consistent with findings in the literature. Importantly, however, remitted patients showed recovery of cognitive function on the Mnemonic Similarity Task. This is the first study that we are aware of to report recovery of function on a high interference, putatively neurogenesis-dependent memory test in a longitudinal sample of hospitalized MDD patients from admission to remission. Our findings are consistent with the neurogenic theory of depression, which posits that a restoration of neurogenesis is linked to recovery from depression.